Sex and age differences in compliance to physician recommendations by surgical patients - S. N. Cherkasov; A. L. Gorbunov; S. S. Saidov; A. V. Fedyaeva; A. A. Sukhov (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2022)
Purpose of the study: analysis of the correlation between the attitude toward compliance with physician's recommendations by surgical patients and their sex and age characteristics.Materials and Methods. Primary data were obtained by questionnaire study of 400 surgical inpatients. Four age comparison groups (18–29 years, 30–44 years, 45–59 years, 60 years and older) among men and women were formed. Significance of differences was determined by comparing the χ2 value obtained in the tetrachoric analysis with the tabulated value for the bilateral distribution. Differences with the 95% probability of null hypothesis rejection were considered significant.Results. Most surgical patients surveyed according to their subjective perception followed the physician's recommendations (75 and 77 out of 100 male and female respondents, respectively), more frequently at a younger age, whereas after 45 years, adherence to the physician's recommendations declined and the proportion of those who were more critical of them increased, which was manifested in their selective implementation. Patients are much less likely to comply with the recommendations to observe the principles of a healthy lifestyle. With increasing age, the share of men who always comply with the principles of a healthy lifestyle decreases, while for women it remains at the same level. As a result, "strict" and "clearly" formulated recommendations are followed more often by patients, and no gender differences are observed in this aspect. More general recommendations (principles of healthy lifestyle) are more often implemented selectively, that is, when they are considered necessary and necessary, and with increasing age the proportion of such attitude among men increases, while among women it remains stable in all age groups. Dependence analysis showed that compliance with the doctor's recommendations in full by the patient regardless of gender did not guarantee his efforts to maintain his own health sufficiently (p > 0,05) or the absence of bad habits (p > 0,05). There was also no correlation between the presence of bad habits and the subjective perception of the sufficiency of efforts to maintain one's own health (p > 0.05).